Climate changes over the past millennium: Relationships with Mediterranean climates - Mann, M. E. (Societa italiana di fisica, 2006)
Evidence is reviewed for climate change and its causes over the interval spanning roughly the past millennium. Particular emphasis is placed on patterns of climate change influencing Mediterranean climates of the Northern Hemisphere. The evidence is taken from studies using high-resolution climate “proxy” data sources, and climate modeling simulations. The available evidence suggests that forced changes in dynamical modes of variability including the North Atlantic Oscillation (NAO) and El Nino/Southern Oscillation (ENSO) have played a key role in the patterns of climate variability in Mediterranean regions over the past millennium.